Exploring Nominalization and Adjectivization in Joko Widodo’s Speech: A Morphological Analysis - Anggun Purnomo Arbi (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
This study focuses at adjectivization and nominalization of derivational morphemes in Joko Widodo's speech. With derivational morphemes changing word meanings and classes, morphology indicates how languages have evolved. Adjectivization turns words into adjectives whereas nominalization converts non-nouns to nouns. These procedures enrich language, increasing the complexity of communication. Speeches are essential for expressing ideas and forming opinions. By examining Joko Widodo's speech, one can gain insight into morphological techniques used in formal situations. This study examines the functions of adjectivization and nominalization in communication using qualitative approaches and document analysis. Findings show that nominalization, which transforms verbs and adjectives into nouns, improves expression, while adjectivization highlights characteristics and features. Both methods help to communicate complex ideas and vivid descriptions. Future research can examine additional examples and circumstances, even if this study deepens our understanding of derivational morphemes in speech. Finally, Joko Widodo's speech serves as an example of how language may be flexible through nominalization and adjectivization. These processes highlight language's flexibility by enhancing meaning and increasing listener involvement. By using these methods, ideas and creativity are effectively communicated. Understanding how language modifies meaning through morphological changes is aided by the findings of this study.